Postharvest Practices and Farmers’ Knowledge in Managing Maize Pests in the Eastern Cape Province, South Africa - Bongumusa Charles Gumede; Simon Kamande Kuria (Insects)
This study aims to establish the pest management approach for pests of stored maize and determine the current control practices. Semi-structured questionnaires were administered to 77 smallholder farmers from 16 villages at King Sabata Dalindyebo local municipality in the Eastern Cape Province of South Africa. The results revealed that about 50% of the farmers had a formal education, the average farm size was 1 hectare, and they were predominantly cultivating yellow maize. Most farmers (57%) cultivated maize for human consumption, income generation, and livestock feeding. The results also showed that metal tanks tended to be the most preferred (81.82%) storage facility for storing maize. Furthermore, the study found that Sitophilus zeamais Motschulsky and Sitotroga cerealella (Olivier) were the major storage insect pests of maize. The storage pests were managed using synthetic pesticides (84.42%), namely aluminium phosphide. This pesticide is a solid formulation for generating gas phosphine for fumigation. The continued indiscriminate use of this pesticide in protecting stored maize in this region could be a health hazard to humans and may result in the development of pest resistance.